Quality Service Strategy in Improving Performance of Puskesmas Service Area of Mranggen District - Nanang Wahyudin (Integrated Journal of Business and Economics (IJBE), 2018)
This study aims to analyze the quality of services available at the health center of Mranggen in order to formulate a strategy to improve the quality of health services of Puskesmas by analyzing the importance and level of performance in six dimensions of service quality (Tangibles, Reliability, Responsiveness, Assurance, Empathy and Accessibility) to produce performance (performance) that can satisfy customers. The data analysis of this research was conducted by qualitative descriptive method, to answer the problem formulation about how to improve the quality of health service of Mranggen in accordance with the quality standard set by the Government, then used "Importance-Performance Analysis" with Cartesian diagram, the number of samples of this study 75 respondents taken from three Puskesmas available at Puskesmas Mranggen. The result of the research shows that the dimension of Responsiveness is the main priority to improve the quality of service because it has the highest importance of 81.3%, while the performance is still low with the level of conformity of 71%, while the next sequence based on the level of conformity is Assurance dimension, Accessibility, Tangibles, Reliability, and Empathy. Thus the whole health center Mranggen considered good enough from the level of customer satisfaction.